Unit costs for non-acute care in Ireland 2016—2019 [version 1; peer review: 2 approved] - Samantha Smith; Jingjing Jiang; Charles Normand; Ciaran O’Neill (HRB Open Research, 2021)
Background: This paper presents detailed unit costs for 16 healthcare professionals in community-based non-acute services in Ireland for the years 2016—2019. Unit costs are important data inputs for assessments of health service performance and value for money. Internationally, while some countries have an established database of unit costs for healthcare, there is need for a more coordinated approach to calculating healthcare unit costs. In Ireland, detailed cost analysis of acute care is undertaken by the Healthcare Pricing Office but to date there has been no central database of unit costs for community-based non-acute healthcare services. Methods: Unit costs for publicly employed allied healthcare professionals, Public Health Nurses and Health Care Assistant staff are calculated using a bottom-up micro-costing approach, drawing on methods outlined by the Personal Social Services Research Unit in the UK, and on available Irish and international costing guidelines. Data on salaries, working hours and other parameters are drawn from secondary datasets available from Department of Health, Health Service Executive and other public sources. Unit costs for public and private General Practitioner, dental, and long-term residential care (LTRC) are estimated drawing on available administrative and survey data. Results: The unit costs for the publicly employed non-acute healthcare professionals have changed by 2–6% over the timeframe 2016–2019 while larger percentage changes are observed in the unit costs for public GP visits and public LTRC (14-15%). Conclusions: The costs presented here are a first step towards establishing a central database of unit costs for non-acute healthcare services in Ireland. The database will help ensure consistency across Irish health costing studies and facilitate cross-study and cross-country comparisons. Future work will be required to update and expand on the range of services covered and to incorporate new data and methodological developments in cost estimation as they become available.